The Effect of Using Google Classroom as an English Learning Media for the Seventh Grade Students at SMP Negeri 1 Bajeng - Fifi Citra Walia; Sukmawati Sukmawati; Muliaty Ibrahim (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2023)
This study aims to determine the effect of using Google Classroom as a medium for learning English on class VII students at SMP Negeri 1 Bajeng. The research method used is a quantitative method with a Quasi Experimental Design research design which consists of two classes, namely the experimental class using Google Classroom and the control class using conventional methods. The sample of this study was the seventh grade students consisting of 29 students for the experimental class and 29 students for the control class. Data collection techniques in this study used pre-test and post-test. The results of this study indicate that the post-test experimental class has a mean value of 87.41 and the post-test control class has a mean value of 76.03. The results of the data analyzed using the independent sample t-test, show that Sig.(2-tailed) is 0.003 lower than 0.05 so that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected so that there is an effect on students' reading comprehension results after using Google Classroom. Based on the results of this study, it can be concluded that the use of Google Classroom as an English learning medium has an effect on seventh grade students at SMP Negeri 1 Bajeng, especially students' reading comprehension.